ROLE OF INTESTINAL MICROBIOTA IN THE PATHOGENESIS OF ATOPIC DERMATITIS - Gasimova, A.Sh.; Huseynova, Sh.M.; Ahmadzada, U.I.; Aghamaliyeva, U.J.; Guliyeva, A.A.; Guliyeva, N.M. (World of Medicine and Biology, 2025)
Atopic dermatitis is a growing public health problem with a rapidly increasing incidence. Molecular and sequencing technologies have shown that the pathogenesis of atopic dermatitis is influenced not only by the skin but also by the gastrointestinal microbiota. The latter plays a crucial role in the formation and regulation of allergic reactions, including those observed in atopic dermatitis. The concept of the “gut-skin axis” has emerged, and studies increasingly demonstrate their bidirectional interaction. The aim of this review is to investigate the role of the gut microbiota and its changes in the pathogenesis of atopic dermatitis. We analyzed data on changes in the gut microbial composition in patients with atopic dermatitis, their relationship with the epidermal barrier function and toll-like receptors, as well as the complex interactions between the microbiota and adaptive immunity. These results support the possibility of using gut microbiota manipulation as a new approach to prevent and reduce the severity of atopic dermatitis.
Keywords: gut microbiota; skin; allergic disorders; atopic dermatitis; immunity